Evaluation of the Use of ESS BAR (Entebe Smart System) Based on Android as A Sajiwa Program Screening Application - Nur Arifatus Sholihah; Harmili Harmili; Luh Putu Sri Yuliastuti (Indonesian Journal of Global Health Research, 2024)
Mental health problems are currently considered a serious problem that requires comprehensive treatment. In this context, the development of ESS-BAR applications has become an interesting and important research topic. The aim of this research is to evaluate the use of the ESS-BAR application as an appropriate SAJIWA (Mental Health Awareness) Program screening application both in terms of measurement content and accuracy values The method used is evaluation of Android-based application development, which is then measured for accuracy and program evaluation using the End User Computing Satisfaction (EUCS) method. This research involved 10 key informants to obtain an evaluation of the application being developed. The research findings show that the evaluation of the Black Box testing of the application being developed went according to the evaluation checklist sheet. Then, testing the accuracy of mental health screening results involving 10 key informants showed that 75% of respondents strongly agreed that the application could be used as a screening measure for someone's mental health. However, in developing ESS-BAR, further evaluation still needs to be carried out regarding personalization and adjustment of user data Conclusions So further development is still needed. The benefits of this program are expected to increase the use of technology in providing mental health services so that follow-up can be done to receive counseling services and subsequent intervention plans according to the problems faced.